Pelatihan Bakery Dalam Meningkatkan Keterampilan Warga Binaan Pemasyarakatan Di Lembaga Pemasyarakatan Pemuda Kelas IIA Tangerang - Fara Ardhika Divayana; Sokhivah Sokhivah (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Inmates who are in correctional institutions receive a negative stigma from society with the inmates being labeled "criminals". This labeling makes inmates feel embarrassed about re-entering society and afraid of not being accepted in their environment. So, to overcome this problem, the Correctional Institution provides guidance for the inmates by including a job training program to add expertise and skills as a provision when the inmates finish serving their prison term. This research uses descriptive qualitative research methods. Data collection was carried out by interviews, observation and documentation. The research results show that bakery training can develop the inmates' skills in the culinary field and improve interaction skills between other inmates and increase the inmates' productivity. By having skills in the culinary field, they can use them to earn a living when they leave the penitentiary.